SMART DOOR HANDLE BERBASIS INTERNET OF THINGS (IOT) DENGAN SENSOR TOUCH KAPASITIF DAN ALGORITMA FUZZY LOGIC - Ahmad Fauzan; Suriati Suriati (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
The development of Internet of Things (IoT) technology offers opportunities to enhance home security through smart devices. This study aims to design and implement an IoT-based Smart Door Handle using a capacitive sensor and a magnetic mounting design that can be easily installed on door handles. The system is equipped with a fuzzy logic model capable of mapping capacitive sensor variables, such as signal amplitude, touch duration, and pattern changes, into real-time threat level decisions. In addition, the device is integrated with notification platforms, namely Blynk and Telegram, allowing users to receive door status information directly and monitor security even when they are away from the location. The test results show that the device can detect touches with adequate accuracy, update security status in real-time, and successfully send notifications to users. The system also allows user management through a web interface, accessible via PC/laptop using mDNS or IP address, and via smartphones using IP address. Based on testing, the system meets the design objectives in terms of monitoring, user management, and real-time notification.